ANALISIS KINERJA KEUANGAN PERUSAHAAN UMUM DAERAH (PERUMDA) AIR MINUM TIRTA MAYANG KOTA JAMBI - Muhammad Najib Ariqza; Rosmeli Rosmeli; Al Parok Al Parok (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the development and financial performance of the Regional Public Water Utility Company (PERUMDA) Tirta Mayang of Jambi City during the period 2015–2024. The company’s development is examined based on business revenue, profit/loss, and number of customers. Meanwhile, financial performance is analyzed using financial ratio analysis, including liquidity ratio (Current Ratio), profitability ratio (Return on Assets/ROA), operational efficiency ratio, and activity ratio (Total Asset Turnover). This research employs a quantitative descriptive method using secondary data in the form of financial statements of PERUMDA Tirta Mayang Jambi City from 2015 to 2024. The data analysis technique involves calculating the growth of each indicator and the average financial ratios to assess the company’s financial condition during the research period. The results indicate that, on average, the development of PERUMDA Tirta Mayang Jambi City shows a positive trend. The average growth of business revenue is recorded at 9.15 percent per year, while the average growth in the number of customers reaches 5.46 percent per year. However, the company’s profit/loss development shows relatively high fluctuations. Based on the financial performance analysis, the average liquidity ratio is categorized as very good (highly liquid). The average profitability ratio (ROA) remains relatively low and falls into the poor category. The average operational efficiency ratio indicates a very efficient (good) condition. Meanwhile, the average activity ratio is considered less effective, suggesting that the utilization of company assets in generating revenue still needs improvement. Based on these findings, it can be concluded that PERUMDA Tirta Mayang Jambi City generally demonstrates positive development. However, improvements in financial performance are still required, particularly in terms of profitability and asset utilization optimization, in order to achieve more sustainable performance in the future